Clinical impact of the interstitial lung disease multidisciplinary service. Issue 8 (18th July 2016) - Jo, Helen E.; Glaspole, Ian N.; Levin, Kovi C.; McCormack, Samuel R.; Mahar, Annabelle M.; Cooper, Wendy A.; Cameron, Rhoda; Ellis, Samantha J.; Cottee, Alice M.; Webster, Susanne E.; Troy, Lauren K.; Torzillo, Paul J.; et al.
ABSTRACT: Background and objective: Multidisciplinary discussions (MDDs) have been shown to improve diagnostic accuracy in interstitial lung disease (ILD) diagnosis. However, their clinical impact on patient care has never been clearly demonstrated. We describe the effect that an ILD multidisciplinary service has upon the diagnosis and management of patients with suspected ILD. Methods: Patients at two specialized centres with suspected ILD underwent ILD multidisciplinary team review (ILD‐MDT) (standard ILD clinic visit and diagnostic review at ILD‐MDD). We compared changes in ILD diagnosis and management at referral to those following the ILD‐MDT. Results: Ninety patients, 60% males (54/90), aged 67.3 years (SD = 11.4) were reviewed for suspected ILD. Overall, the ILD‐MDT resulted in a change in specific ILD diagnosis in 48/90 (53%) patients. Of the 27 patients referred with a diagnosis of idiopathic pulmonary fibrosis (IPF), the diagnosis was changed at MDD in 10 patients. In contrast, seven patients had their diagnosis changed to IPF. There was also a significant reduction in 'unclassifiable' diseases and disease behaviour classifications provided additional information beyond ILD diagnosis. Conclusion: Dedicated tertiary ILD‐MDT service has an important clinical impact on the care of the ILD patient, with frequent changes in ILD diagnosis and subsequent management. Further research to investigate long‐term clinical outcomes of ILD‐MDT is required. Abstract : We demonstrate a significant change in specific interstitial lung disease (ILD) diagnosis in ILD patients assessed at ILD referral centres. This allows specific management to be implemented, which is critically important in patients with idiopathic pulmonary fibrosis (IPF), a disease associated with the poorest prognosis but now with specific therapy available.